Distribution, morphology and habitats of saline wetlands: a case study from Monegros, Spain - C. CASTAÑEDA; J. HERRERO; J.A. CONESA (Geologica Acta, 2013)
Wetlands in semiarid regions have received less attention than wetlands in humid-temperate areas, and the limited amount of information has resulted in little regulatory recognition. A comprehensive map of the saline wetlands that occur in karstic depressions in the semiarid region of Monegros, NE Spain, was developed from historical data, topography, and surveys of vascular flora. Playa-lakes and other saline depressions are expressions of solution dolines largely founded on groundwater dynamics and favored by the limestone and gypsum-rich substrate. Substrate composition, groundwater dynamics, and the network of infilled valleys are key factors in the distribution of the wetlands. In spite of the anthropogenic imprint, wetlands morphometrics are the expression of geological processes. Significant correlations were found between basin area and depth, and between elongation and substrate composition. The predominantly subelongated shape of the Monegros saline wetlands (MSW) reflects their origin and a geometry strongly influenced by fractures. Grouping the MSW based on geological and vegetation features, provide a predictable relationship of surficial processes with the occurrence of otherwise complex and undetectable hydrological connectivity. Our ten geology-based Groups showed a high intra-group variation in depth, elongation, and vegetation cover. The eight vegetation-based categories mirror the gradation in flooding frequency and the soil salinity of MSW. The significant contrasts existing in-between the groups of wetlands and the disclosure of their causal factors provides a functional perspective at the landscape scale. This approach will help to monitor the ongoing environmental alterations associated with new on-farm irrigation developments.